Clinical impact of molecular subtyping of pancreatic cancer - Xu, Zhou; Hu, Kai; Bailey, Peter; Springfeld, Christoph; Roth, Susanne; Kurilov, Roman; Brors, Benedikt; Greß, Thomas; Buchholz, Malte; An, Jingyu; Wei, Kongyuan; Peccerella, Teresa; et al. (Frontiers in cell and developmental biology, 2021)
Pancreatic ductal adenocarcinoma is a highly lethal malignancy, which has now become the seventh commonest cause of cancer death in the world, with the highest mortality rates in Europe and North America. In the past 30 years there has been some progress in 5-year survival (rates increasing from 2.5% to 10%, but this is still extremely poor compared to all other common cancer types. Targeted therapies for advanced pancreatic cancer based on actionable mutations have been disappointing, with only 3-5% showing even a short clinical benefit. There is however a molecular diversity beyond mutations in genes responsible for producing classical canonical signalling pathways. Pancreatic cancer is almost unique in promoting an excess production of other components of the stroma, resulting in a complex tumour microenvironment that contributes to tumour development, progression and response to treatment. Various transcriptional subtypes have also been described. Most notably there is a strong alignment between the Classical/Pancreatic Progenitor and Quasi-mesenchymal/Basal-like/Squamous subtype signatures of Moffit, Collinson, Bailey, Puleo and Chan-Seng-Yue, which have potential clinical impact. Sequencing of epithelial cell populations enriched by laser capture microscopy combined with single cell RNA sequencing has revealed the potential genomic evolution of pancreatic cancer as being a consequence of a gene expression continuum from mixed Basal-like and Classical cell populations within the same tumour, linked to allelic imbalances in mutant KRAS, with metastatic tumours being more copy number-unstable compared to primary tumours. The Basal-like subtype appears more chemoresistant with reduced survival compared to the Classical subtype. Chemotherapy and/or chemoradiation will also enrich for the Basal-like subtype. Squamous/Basal-like programmes facilitate immune infiltration compared with the Classical-like programmes. The immune infiltrates associated with Basal and Classical type cells are distinct, potentially opening the door to differential strategies. Single cell and spatial transcriptomics will now allow single cell profiling of tumour and resident immune cell populations that may further advance subtyping. Multiple clinical trials have been launched based on transcriptomic response signatures and molecular subtyping including COMPASS, Precision Promise, ESPAC6/7, PREDICT-PACA, and PASS1. We review several approaches to explore the clinical relevance of molecular profiling, to provide optimal bench-to-beside translation with clinical impact.
Gesehen am 16.12.2021